On T-Fuzzy Ideals in Nearrings - Muhammad Akram (International Journal of Mathematics and Mathematical Sciences)
We introduce the notion of fuzzy ideals in nearrings with respect to a t-norm T and investigate some of their properties. Using T-fuzzy ideals, characterizations of Artinian and Noetherian nearrings are established. Some properties of T-fuzzy ideals of the quotient nearrings are also considered.